Web Based College Automation System - Chavan, SS; Vejare, GS; Dsouza, SG; N.M.Shivsharan, (International Journal of Computer Sciences and Engineering, 2020)
In this paper focuses on a College Automation system is an Web Based project. Which is helpful for students as well as the Faculties, Library and Admin (Record Manager) In the existing system all the activities are done manually. It is very costly and time consuming. In our proposed system, Student can view college related details like assignment, notes, notices, view available books details, attendance, library status etc. Librarian can record new book details also issue book and renew book, etc. Faculty can upload assignment, mark, student attendance, etc. The proposed work has three modules: 1.Student 2.Admin 3.Staff. In Student module student need to register after the registration He/She need to be verify their email. Only after verification of email He/She can login into system. In Admin module, admin can handle and view the all record which store in database. This college automation system access anytime and anywhere, whenever user wants. College Automation System enables colleges to manage enrollment, students, faculty, attendance, fees, scheduling, assignments, grades and library of the institution. This system has easy interface. To overcome the problem of manual system we have developed this system.